A space provided to listen: an interview study of African American and Latino alumni of Agriculture Stem Programs - Holmes, JohnElla J. (Kansas State University, 2015)
African American and Latino students continue to experience lower retention and higher attrition rates then their White counterparts. The aim of this qualitative interview study was to understand how African American and Latino students at a predominantly White institution (PWI) achieved graduation in Agriculture-STEM (A-STEM) disciplines. Based on the global need for more A-STEM and STEM professionals and the under-representation of African American and Latino students in the fields, there appeared to be a gap in the research on this population and success attributes with respect to completing undergraduate degrees. There was a tendency in the literature toward examining African American and Latino students utilizing the deficit model. This study explores the lived experiences of two African American and one Latino alumni of A-STEM programs. Understanding the life stories, via counter narratives, of these students may help universities develop stronger support for student success in college for not only African American and Latino students, but for all students in A-STEM disciplines. Critical Race Theory was the framework used for the analysis and the interpretation of the data in this study. The data consisted of interview transcripts, timeline, documents, photographs, and e-mail conversations. Communicating the findings in qualitative interview studies is the result of constructing the experiences and meanings of events through the eyes of the participants in a manner that portrays a representation of their experiences. Each participant’s counter narratives were created to highlight salient patterns reflected in their experiences. The writing around the participants’ experiences, and the interrogation of data allowed for the identification of patterns that were consistent with each participant’s stories and their individual unique details. The findings revealed: (a) ethnic minority students want faculty and administrators who looked like them because having someone to understand their experiences as people of color in PWI is needed; (b) the need for organizations that support ethnic minority student academic and social success, which in turn helps to create a sense of belongingness and a more inclusive campus climate; (c) more overall faculty support in and out of the classroom; and (d) opportunities for involvement in faculty-led research projects.
Keywords: Ethnic minority; Agriculture Science Technology Engineering and Mathematics (A-STEM); Retention; Counter narrative; Critical Race Theory (CRT); Higher Education (0745)